The Reconstruction of Rural Society in the Aftermath of the Mayan Rebellion of 1847 - Angel, Barbara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1993)
AbstractIn 1847, Mayan peasants under the leadership of their traditional caciques rose up against the creole authorities of the state of Yucatán. This rebellion, known to contemporaries and later historians as the Caste War, has been described as the most prolonged and bloody resistance on the part of an indigenous group in the Americas since the Spanish conquest. While the rebellion itself poses challenging questions regarding the nature of peasant involvement in movements for social change, this paper deals with the government's efforts to restore order in the countryside, and the response of the Mayan campesinos as they found themselves caught up in a struggle which they could not avoid. The study focuses on a specific region of the Yucatán peninsula, the Sierra or Puuc, which, because of its strategic location between the northwest region dominated by the government and the hinterland controlled by various rebel groups, played a pivotal role in the war.The paper assesses the results of the government's pacification policy, examines the question of migration and flight of refugees into zones of refuge, and discusses the survival strategies adopted by Mayan peasants in the communities of the Puuc. The study also addresses the role of non-combatants in guerrilla warfare, and their ambiguous relationship with both sides in the conflict, as potential allies or enemies.